Ultra-Wideband Transmitters based on M-Sequences for High Resolution Radar and Sensing Applications - Sewiolo, Benjamin; Lämmle, Benjamin; Weigel, Robert (Sixth Conference on Ph.D. Research in Microelectronics and Electronics, 2010)
In this paper we present a novel ultra-wideband transmitter architecture for high resolution radar and sensing applications up to 30GHz. The concept for pulse compression is based on maximal-length sequences to reduce the peak-to-average power ratio. The proposed transmitter consists of a 29-1 linear feedback shift register (LFSR) to generate the radar signal and a fully differential broadband amplifier. A variable gain control has been implemented to provide high sensitivity and decrease the dynamic range. The presented circuit architecture permits the possibility of upconversion, which drastically increases the operational flexibility of the radar system.
elib2cris::1512001600,sewiolo2010